Charles Taylor - Abbey, Ruth, 1961- (Contemporary philosophy in focus., 2004)
Taylor is beyond question one of the most distinctive figures in the landscape of contemporary philosophy. His most recent writings have seen him branching into the study of religion. Written by a team of international authorities, this collection will beread primarily by students and professionals.